Hubungan Antara Masa Kerja dan Penggunaan Alat Pelindung Diri dengan Keluhan Penglihatan Pada Pekerja di Bengkel Las Kota Manado - Eby Tappi; Woodford Baren Joseph; Sri Seprianto Maddusa (Universitas Pahlawan Tuanku Tambusai, 2026)
Welding workers rank second in terms of the percentage of workers suffering eye injuries due to direct exposure to foreign objects such as sparks and light. Length of service and eye problems. Longer working hours increase the risk of eye disorders because workers are frequently exposed to light and welding fumes. Sore eyes, red eyes, itching, double vision, and blurred vision are among the vision problems that may arise from worker non-compliance. This study aims to determine whether there is a relationship between work period and the use of PPE with visual complaints in workers in the Manado City welding workshop The type of research is analytical observational with a cross-sectional approach carried out in November 2025-April 2026. The population in this study were all workers in the welding workshop as many as 35 workers and using total sampling. Data collection was carried out through interviews using questionnaires and direct observation. Data were analyzed univariately, bivariately. using the Spearman correlation test with a significance level of p <0.05. The results of the study showed that 11 (31.4%) respondents with new work period, 14 (40.0%) respondents with medium work period and 10 (28.6%) respondents with long work period. Respondents with low frequency of PPE use were 15 (42.9%), moderate 18 (51.4%) and high 2 (5.7%) respondents and respondents with complaints of light frequency of visual complaints were 8 (22.9%), moderate 23 (65.7%) and severe 4 (11.4%) respondents. The results of the spearman correlation test showed a relationship between work period and use of PPE with visual complaints in workers in the Manado city welding workshop with p-value.s ​​(0.008) and (0.001) respectively.